Integrative Model for Quantitative Evaluation of Selection Telecommunication Tower Site - Janah A. Asassfeh; Mokhled AlTarawneh; Fadiya Samson (Universitas Ahmad Dahlan, 2018)
This paper analyzes the weight of impact factors on selection the antenna places for mobile telecommunication system in Jordan. The new technique plays a lead role in divided area and selects the place of antennas' sites. The main objective of this research is to minimize the antenna numbers in order to reduce the cost. Research follows flowcharting categories and stages as: The first stage aim to classify the effective factors on the: signal radius, better position of antenna from candidate points, reserved area, and non-preferring position. The second stage focuses on finding the effective weight of these factors on the decision. The third stage suggest the new proposed approach by implement the MCLP and P-center problems in linear function. The last stage has the pseudo code for the proposed approach, where the proposed approach provides the solution that helps the planners in telecommunication industry and in related government agencies make informed position of the antennas.